Synthesis of Biocompatible Double‐Tailed Nonionic Surfactants and Their Investigation for Niosomal Drug‐Loading Applications. Issue 4 (1st May 2019) - Ali, Imdad; Shah, Muhammad Raza; Nadeem, Said; Saad Ali, Heyam; Saifullah, Salim; Ahmed, Farid; Imran, Muhammad
Abstract: Nonionic surfactants are capable of self‐assembling and thus are of vital importance for designing various drug‐delivery systems. This study reports the synthesis, characterization, biocompatibility, and drug‐loading potential of sulfanilamide‐based novel nonionic surfactants. These surfactants were synthesized in a single‐step reaction and characterized using nuclear magnetic resonance (NMR), electron impact mass spectroscopy, and fourier‐transforminfrared spectroscopy (FTIR). Critical micelle concentration (CMC) of the synthesized nonionic surfactants was determined using a ultraviolet–visible (UV) spectrophotometer. The surfactant potential for niosomal vesicles was explored using simvastatin as a model drug. The drug‐loaded vesicles were screened for shape, size, size distribution, and percent drug entrapment efficiency (EE%) using atomic force microscopy (AFM), zeta potential, and UV–visible spectrophotometry. Biocompatibility of the synthesized surfactants was investigated through blood hemolysis and cell toxicity assays. Synthesized nonionic surfactants revealed lower CMC values of 0.045–0.095 mM and entrapped an improved amount of drug upon self‐simplifying in niosomal vesicles. Findings of the study confirm these nonionic surfactants as hemocompatible and nontoxic candidates for vesicular drug‐delivery applications.